Minimum wage setting and standards of fairness - David A. Green; Kathryn Harrison (Institute for Fiscal Studies (IFS), 2010)
We examine the setting of minimum wages, arguing that they can best be understood as a reflection of voters' notions of fairness. We arrive at this conclusion through an empirical investigation of the implications of three models, considered in the context of policy setting by sub-units in a federation: a competing interests group model; a constrained altruism model; and a fairness based model. In the latter model, voters are interested in banning what they view to be unfair transactions, with the notion of fairness based on comparisons to the 'going' unskilled wage. We use data on minimum wages set in the ten Canadian provinces from 1969 to 2005 to carry out the investigation. A key implication of the models that is borne out in the data is that minimum wages should be set as a positive function of the location of the unskilled wage distribution. Together, the results indicate that minimum wages are set according to a 'fairness' standard and that this may exacerbate movements in inequality.
Keywords: J38; H73; D78; 330; Lohnverhandlungen; Mindestlohn; Altruismus; Gerechtigkeit; Wahlverhalten; Kanada